Frequency of Carcinoma Prostate in Patients with Clinically Diagnosed Benign Prostatic Hyperplasia (BPH) and Prostate Specific Antigen d" 4ng/ml (Bangladesh Journal of Urology, 2020)
Objectives: The present study was carried out in the Department of Urology, Sir Salimullah Medical College Mitford Hospital Dhaka between July 2009 to May 2010. To determine the frequency of prostate cancer in patients with BPH & PSA level d” 4 ngm/ml.Methods: A total of 198 subjects aged above 50 years with serum PSA level of not more than 4.0 ng per milliliter , no suspicious nodule on digital rectal examination , homogenous echogenicity of prostate on ultrasonographic findings, peak urinary flow rate (Qmax) < 10ml/sec in uroflowmetry and no clinically significant coexisting conditions were included in the study. All the patients presented with obstructive urinary symptoms attended at four tertiary hospitals in Dhaka city during the study period were evaluated with clinical history, physical examination and some investigations. All the patients were treated with transurethral resection of prostate (TURP). Chips were collected carefully and sent for histopathology.Results: The mean age was 65.1 ± 7.3 years. About 32% of patients had serum PSA level 2 ng/ml or less and 68.2% more than 2 ng/ml. The peak urinary flow rate was 7.2 ± 2.7 ml/sec. One hundred and ninety three (98%) patients were diagnosed as having benign prostatic hyperplasia (BPH) on histopathological examination and 5(2.5%) as having prostate carcinoma.Conclusion: Prostate cancer is not rare among men with PSA levels of 4.0 ng per milliliter or lessBangladesh Journal of Urology, Vol. 15, No. 2, July 2012 p.44-47